Analisis Implementasi Pengelolaan Kelas Dan Pengelolaan Peserta Didik - Marsya Indah Yunita; Hesti Iswandayani; Nita Dwi Rahayu April; Fingka Wahyu Anggraini; Sela Rizki Azkiyah; Bahtiyar Heru Susanto (STIKes Ibnu Sina Ajibarang, 2024)
: Good classroom and student management will have a positive impact on the learning process, create an environment conducive to student growth and development, and improve the overall quality of education. Class management and students in Indonesia have experienced various developments and transformations in line with changes in educational approaches, government policies and technological developments. However, challenges such as the lack of adequate educational facilities and infrastructure, disparities between regions in access to education, and improving the quality of teaching staff remain the main focus in efforts to improve the quality of education in Indonesia. Classroom management refers to the strategies and techniques used by educators to create a conducive, orderly and effective learning environment. This includes the physical setting of the classroom, rules and procedures, and approaches to dealing with student behavior. Meanwhile, student management involves an individual approach in understanding and meeting each student's learning needs, including differentiation strategies, providing motivation, and emotional support. This article highlights the importance of good classroom management skills for teachers to increase student participation and achievement, and emphasizes the important role of student management in creating personalized and inclusive learning experiences. Case studies and practical recommendations are included to provide guidance for educators in implementing these strategies effectively.